2010
DOI: 10.1094/pdis-94-7-0891
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoctonia Web Blight Development on Container-Grown Azalea in Relation to Time and Environmental Factors

Abstract: Rhizoctonia web blight, caused by binucleate Rhizoctonia spp., is an annual problem in the southern United States on container-grown azaleas (Rhododendron spp.) that receive daily irrigation. Disease progress was assessed weekly from mid-May to mid-September on nursery-grown plants at three locations in Mississippi and Alabama in 2006, 2007, and 2008. Disease onset, defined as the appearance of blighted leaves at the exterior canopy of at least one plant, occurred on average on 20 July, and calendar date was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Web blight symp toms typically appear in July and August, but can occur as early as June and as late as September (2,7,8,14). The most common symp tom is complete foliar necrosis o f individual leaves, with marginal leaf necrosis occurring less frequently.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Web blight symp toms typically appear in July and August, but can occur as early as June and as late as September (2,7,8,14). The most common symp tom is complete foliar necrosis o f individual leaves, with marginal leaf necrosis occurring less frequently.…”
mentioning
confidence: 99%
“…Temporal studies on Rhizoctonia web blight on azalea in south ern M ississippi have reported several different weather conditions that are conducive for disease development (4)(5)(6)(7)(8). Rhizoctonia web blight development on azalea was initially correlated with air tem peratures between 25 and 30°C for 6 to 8 h per day, relative humid ity >95% for >8 h per day, and/or leaf wetness for >6 h per day (7).…”
mentioning
confidence: 99%
See 3 more Smart Citations